Ijtihadat 'Umar ibn al-Khattab al-idariyah fi daw' maqasid al-shari'ah al-Islamiyah = Umar b. al-Khattab's ijtihads in administration based on maqasid al-syari'ah / Jalal Alwan Salman - Salman, Jalal Alwan (2013)
This thesis included studying the Ijtihad of Umar B. Al-Khattab (May Allah be pleased with him) in light of the purposes of Shariah. This was accomplished by demonstrating his Ijtihad in managing the Islamic state as the leader and managing body of its affairs, analyzing the motives and incentives for those Ijtihad and the methods he adopted for implementing them as well as the objectives that he intended to achieve through such Itjihad, and discussing those motives, methods and objectives to identify the extent to which those Ijtihad had successfully attained the purposes of the Shariah. The current study aims to present an administrative purpose-based perspective by presenting an ideal model in achieving the purposes of the Shariah which is represented by the administrative personality of Umar B. Al-Khattab (May Allah be pleased with him), explain the relationship between Ijtihad and the management science and explain his focus on the management science in his struggle to establish a state that complies with the purposes of the Shariah. The study has been conducted by adopting a documentary-based approach that relies on induction and investigation of narrations about Umar B. Al-Khattab (May Allah be pleased with him) in collecting its content. The adopted approach also emphasizes the theoretical critical analysis of the study’s topics by inducting sayings of Scholars and specialists of sciences relevant to the topics of this study and analyzing them. Moreover, the study relies on the historical approach to relate the study to a historical past era despite its analysis according to the modern administrative perspective. The study illustrated the impact of Islam upon Umar B. Al-Khattab’s (May Allah be pleased with him) administrative personality reflected by the alteration of his standards in evaluating issues starting from setting objectives and principles that he strived to bring in compliance with the Shariah. Thus, he confirmed principles that came in compliance with the Shariah and discarded those that conflicted with it. In addition, he changed means that help achieve those objectives since they were unjustified by their noble purposes once found to be void. The study illustrated the clarity of Umar B. Al-Khattab’s (May Allah be pleased with him) administrative personality by focusing on the administration and the use of Ijtihad as one of its tools and the establishment of an administrative system for the state which is flexible enough not to conflict with principles of the Shariah, while emphasizing Shura (collaborative opinion), preserving centralization of decision-making, comprehending happenings based on principles of the Shariah, and making use of the existing systems even of their resources were non-Islamic civilizations as long as they did not contradict with the Shariah principles.